Induction of macrophage parasiticidal activity by Staphylococcus aureus and exotoxins through the nitric oxide synthesis pathway. - Cunha, F Q (1993)
Murine peritoneal macrophages stimulated in vitro with killed Gram-positive bacteria Staphylococcus aureus or its membrane components in the presence of interferon-gamma (IFN-gamma) expressed high levels of nitric oxide (NO) synthase and produced large amounts of NO in a dose-dependent manner. This is not due to the contamination by Gram-negative endotoxin because the stimulatory activity was not affected by the addition of polymyxin B. The expression of the NO synthase and the synthesis of NO by macrophages stimulated with toxic shock syndrome toxin-1 (TSST), lipoteichoic acid (LTA) or killed whole S. aureus together with IFN-gamma was inhibited by the glucocorticoid, dexamethasone or by the specific inhibitor of NO synthesis, L-N-iminoethyl-ornithine (L-NIO). The exotoxins together with IFN-gamma also activated macrophages to kill the intracellular parasite Leishmania major. The leishmanicidal activity was completely inhibited by L-NIO.